If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x(4x + 3) = 0 Reorder the terms: 3x(3 + 4x) = 0 (3 * 3x + 4x * 3x) = 0 (9x + 12x2) = 0 Solving 9x + 12x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3x'. 3x(3 + 4x) = 0 Ignore the factor 3.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(3 + 4x)' equal to zero and attempt to solve: Simplifying 3 + 4x = 0 Solving 3 + 4x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 4x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 4x = 0 + -3 4x = 0 + -3 Combine like terms: 0 + -3 = -3 4x = -3 Divide each side by '4'. x = -0.75 Simplifying x = -0.75Solution
x = {0, -0.75}
| 13x-7=42+6x | | 12r+36=2r+10-3r | | (x-9)(x-9)=0 | | (8a+6)2=34 | | 13-8y=5y+2 | | 2c+3=4c-4 | | 150=4.5t | | (18-7)+1=-9 | | 20+2n=52 | | 81-18s+s^2=0 | | -8+10=12 | | 2/7=j+3 | | -29=7n-8 | | -2x-5=10 | | 5s^7-7s-35x+49=0 | | (6)(-4)(-3)= | | w^2-4w=-21 | | 3x+2iy=6+10i | | 27x^2-3x+4=0 | | 21x+12=6x-3 | | 2-(3)x=4 | | 8x-3x=-1 | | 5+2(3x-4)=3x-2(6x+3) | | -45=-3x | | 5n+77=12n | | (X+2)(3x)=(x+2)(6) | | 5n^2+37n+14=0 | | 2w^2-4w+30=w^2+9 | | 4x-5y=2 | | -17-x=-13 | | 0.06x+0.40(100-x)=50 | | 1.25x=2.25 |